Chromosome-level genome assemblies of Channa argus and Channa maculata and comparative analysis of their temperature adaptability. Issue 10 (21st October 2021) - Ou, Mi; Huang, Rong; Yang, Cheng; Gui, Bin; Luo, Qing; Zhao, Jian; Li, Yongming; Liao, Lanjie; Zhu, Zuoyan; Wang, Yaping; Chen, Kunci
Abstract: Background: Channa argus and Channa maculata are the main cultured species of the snakehead fish family, Channidae. The relationship between them is close enough that they can mate; however, their temperature adaptability is quite different. Results: In this study, we sequenced and assembled the whole genomes of C. argus and C. maculata and obtained chromosome-level genome assemblies of 630.39 and 618.82 Mb, respectively. Contig N50 was 13.20 and 21.73 Mb, and scaffold N50 was 27.66 and 28.37 Mb, with 28, 054 and 24, 115 coding genes annotated for C. argus and C. maculata, respectively. Our analyses showed that C. argus and C. maculata have 24 and 21 chromosomes, respectively. Three pairs of chromosomes in C. argus correspond to 3 chromosomes in C. maculata, suggesting that 3 chromosomal fusion events occurred in C. maculata . Comparative analysis of their gene families showed that some immune-related genes were unique or expandable to C. maculata, such as genes related to herpes simplex infection. Analysis of the transcriptome differences related to temperature adaptation revealed that the brain and liver of C. argus rapidly produced more differentially expressed genes than C. maculata . Genes in the FoxO signalling pathway were significantly enriched in C. argus during the cooling process ( P < 0.05), and the expression of 3 transcription factor genes in this pathway was significantly different between C. argus and C. maculata ( P < 0.01). Conclusions: C. maculata may have higher resistance to certain diseases, whereas C. argus has a faster and stronger response to low-temperature stress and thus has better adaptability to a low-temperature environment. This study provides a high-quality genome research platform for follow-up studies of Channidae and provides important clues regarding differences in the low-temperature adaptations of fish.